(untitled) (Global Journal of Management and Business Research, 2018)
Every religion represents a symbolic meaning to food and drinks by having rules to regulate their consumption. This is why certain religions forbid and restrict the consumption of certain food completely or at certain time. Like Islam, there are two terms that denote Islamic prohibitions and restrictions on food, which are ’Haram’ means unlawful or prohibited and ’Halal’ means lawful or permitted. In Bangladesh Muslims comprise 90.4% of the POPULATION and peoples are used to take Halal foods because they know about the benefits of Halal foods especially young Bangladeshi compare to the non-Muslim. However, Philippine Muslims only comprise of 14% from the population, which those are practicing Islam, most of the people of Philippines are Christians. Despite of cultural barrier, Muslims in Philippines have the potential to maximize their contribution if only the uniqueness that they have could be seriously utilized about the benifits of having halal foods.